Sustainable Open Production of Short-Medium-Chain Length Polyhydroxyalkanoates from Crude Glycerol in Batch and Fed-Batch Bioreactors by Pseudomonas Frigusceleri mpc6 - Poblete-Castro, I; Gutierrez-Urrutia, I (American Chemical Society, 2025)
Nonsterile microbial synthesis of chemicals offers a promising route to reducing production costs and establishing sustainable processes. Here, we investigated polyhydroxyalkanoate (PHA) production from glycerol by different Pseudomonas strains under nonsterile conditions at varying NaCl concentrations. There was a negative correlation between PHA synthesis and increasing salt levels for P. putida H and KT2440. In contrast, P. frigusceleri MPC6 exhibited, for the first time, enhanced PHA production on glycerol in the presence of 20 g L-1 NaCl. In open-batch bioreactors, the strain MPC6 produced 0.03 g L-1 h(-1) PHA (42 wt%) from crude glycerol and remained the dominant member of the bacterial community (>98%). We then developed a nonsterile fed-batch process that achieved 52.5 g L-1 of total biomass using a carbon-limiting feeding scheme. A DO-stat feeding approach during nitrogen limitation resulted in a PHA volumetric productivity of 0.47 g L-1 h(-1) with PHA comprising 45% of the biomass. The major monomer in the polymeric chain was 3-hydroxybutyrate (PHB, 87-89%), with the remainder as mcl-PHA. This study demonstrates that halotolerant bacteria can produce high levels of biopolymers under mild salinity conditions that are less corrosive than those in high-salt systems while avoiding sterilization steps, thereby lowering the operating costs of the bioprocess.